LIFESTYLE AND PHYSICAL FITNESS IN EARLY SCHOOL-AGE CHILDREN - Podstawski, Robert; Zwolińska, Danuta; Borowska, Klaudia; Boraczyński, Michał; Omelan, Aneta (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Aim of the study: the aim of the study was determining relation between selected health behaviour aspects and level of physical fitness in 1 st - 3 rd grade pupils at primary school in Malbork (Pomorskie province). Materials and Methods: the research was conducted in 2009 among 153 children aged 7-10 years. The research group consisted of 80 girls and 73 boys. The diagnostic survey method with use of a questionnaire technique and a set of indirect motor trials was applied. Results: the research has shown that the health behaviours of young Polish children do not differ from their peers in other countries. The largest percentage of early school-age children in Malbork achieved the average level of physical fitness (57.0%), while the percentage of students with low (22.0%) and high (21.0%) level was similar. Conclusions: the connection between pro-health attitudes of early school-age children (i.e., leisure activities, own health condition, nutrition and the use of drugs) and the level of their physical fitness was not ascertained.